2019
DOI: 10.1111/tri.13467
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic burden of infections in hospitalized solid organ transplant recipients compared with the general population in Canada – a retrospective cohort study

Abstract: Infections continue to be a major cause of post-transplant morbidity and mortality, requiring increased health services utilization. Estimates on the magnitude of this impact are relatively unknown. Using national administrative databases, we compared mortality, acute care health services utilization, and costs in solid organ transplant (SOT) recipients to nontransplant patients using a retrospective cohort of hospitalizations in Canada (excluding Manitoba/Quebec) between April-2009 and March-2014, with a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…They did not report mortality in transplant subgroups and it is possible that a large, less sick kidney transplant population could have contributed to a lower mortality. Hamandi et al published a large retrospective cohort study from Canada, and they also found lower mortality in SOT groups compared with the general population (7.6% vs 12.5%) but SOT patients had higher acute care health services utilization and costs . Readmissions and hospital length of stay were longer in the SOT population in our study suggestive of higher healthcare cost and utilization.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…They did not report mortality in transplant subgroups and it is possible that a large, less sick kidney transplant population could have contributed to a lower mortality. Hamandi et al published a large retrospective cohort study from Canada, and they also found lower mortality in SOT groups compared with the general population (7.6% vs 12.5%) but SOT patients had higher acute care health services utilization and costs . Readmissions and hospital length of stay were longer in the SOT population in our study suggestive of higher healthcare cost and utilization.…”
Section: Discussionsupporting
confidence: 57%
“…16 In our study, sepsis-associated organ failure rates were higher in all the transplant groups; however, it did not adversely affect overall cohort study from Canada, and they also found lower mortality in SOT groups compared with the general population (7.6% vs 12.5%) but SOT patients had higher acute care health services utilization and costs. 23 Readmissions and hospital length of stay were longer in the SOT population in our study suggestive of higher healthcare cost and utilization.…”
Section: Discussionmentioning
confidence: 49%
“…3 In contrast to the study by Gotur et al, in a Canadian study, Hamandi et al showed that length of stay and the rates of home discharge were more favorable to SOT recipients. 1 Similar to above mentioned study, in a study focused on liver transplant recipients only, Wang et al showed that sepsis was associated with higher mortality, prolonged mechanical ventilation, and increased requirement for renal replacement therapy. All these finding were reflecting in greater economic burden in SOT recipients with sepsis.…”
Section: Discussionmentioning
confidence: 67%
“…Infectious diseases specialists are often consulted for the management of infections, leading to fast treatment of sepsis with antibiotics, antifungals, and vascular resuscitation. 1,9,21 The study published by Kalil et al showed that SOT patients had similar rate of septic shock with non-SOT patients (p ¼ 0.241) but higher SOFA score (p < 0.0001), and they were more likely to have multiorgan failure (p < 0.001). 9 SOT recipients compared with non-SOT patients have lower platelets (p < 0.001) and white blood cell counts (p ¼ 0.032), on presentation, were more likely to have a nosocomial infection (p < 0.0001) and less likely to receive appropriate initial empiric treatment (p < 0.001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation